Comparison of the cyclic fatigue resistance of One Curve, F6 Skytaper, Protaper Next, and Hyflex CM endodontic files - Charlotte Gouédard; Laurent Pino; Reza Arbab-Chirani; Shabnam Arbab-Chirani; Valérie Chevalier (Restorative Dentistry & Endodontics)
ObjectivesThis study compared the cyclic fatigue resistance of One Curve (C wire) and F6 Skytaper (conventional austenite nickel-titanium [NiTi]), and 2 instruments with thermo-mechanically treated NiTi: Protaper Next X2 (M wire) and Hyflex CM (CM wire).Materials and MethodsTen new instruments of each group (size: 0.25 mm, 6% taper in the 3 mm tip region) were tested using a rotary bending machine with a 60° curvature angle and a 5 mm curvature radius, at room temperature. The number of cycles until fracture was recorded. The length of the fractured instruments was measured. The fracture surface of each fragment was examined with a scanning electron microscope (SEM). The data were analyzed using one-way analysis of variance and the post hoc Tukey test. The significance level was set at 0.05.ResultsAt 60°, One Curve, F6 Skytaper and Hyflex CM had significantly longer fatigue lives than Protaper Next X2 (p < 0.05). No statistically significant differences were found in the cyclic fatigue lives of One Curve, F6 Skytaper, and Hyflex CM (p > 0.05). SEM images of the fracture surfaces of the different instruments showed typical features of fatigue failure.ConclusionsWithin the conditions of this study, at 60° and with a 5 mm curvature radius, the cyclic fatigue life of One Curve was not significantly different from those of F6 Skytaper and Hyflex CM. The cyclic fatigue lives of these 3 instruments were statistically significantly longer than that of Protaper Next.